2020
DOI: 10.3390/ijerph17134718
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Exposure to Adverse Childhood Experience: Depressive Symptoms, Suicide Intensions and Suicide Plans among Senior High School Students in Nanchang City of China

Abstract: This study tested relationships between different types of adverse childhood experiences (ACE) and depressive symptoms, suicide intensions, suicide plans and examines the cumulative effects of adverse childhood experience on depressive, suicide intentions and suicide plans among senior high school students. We conducted a survey among five senior high schools in Nanchang city, which were selected through stratified random cluster sampling. Among the 884 respondents, 409 were male (46.27%), and 475 were female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
11
1
Order By: Relevance
“…This study that 51.5% of the respondents had at least one ACE, which was equal to that of MSM reported by Ding (51.4%) [30] and higher than that of the general population reported by Edwards (34.6%) [31], Lin (34.16%) [32] and Eleonora lob (24%) [33]. Among all types of ACEs, the reported rates of emotional neglect and emotional abuse among participants were higher, accounting for 22.6% and 22.3%, respectively.…”
Section: Discussioncontrasting
confidence: 40%
“…This study that 51.5% of the respondents had at least one ACE, which was equal to that of MSM reported by Ding (51.4%) [30] and higher than that of the general population reported by Edwards (34.6%) [31], Lin (34.16%) [32] and Eleonora lob (24%) [33]. Among all types of ACEs, the reported rates of emotional neglect and emotional abuse among participants were higher, accounting for 22.6% and 22.3%, respectively.…”
Section: Discussioncontrasting
confidence: 40%
“…As discussed in the previous study (Butchart et al, 2006), there is a great deal of uncertainty around the estimates of the frequency and severity of ACEs worldwide due to inconsistencies in the measurement and definition of ACEs. In addition, it is worth noting that most previous studies assessed ACEs in the elder population (McLaughlin et al, 2010;Merrick et al, 2017), while few studies were conducted in young adults (Jia et al, 2020;Cheung et al, 2021). Much violence against children remains largely hidden and unreported because of fear and stigma and the societal acceptance of this type of violence (Pinheiro, 2006;Norman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ACEs were attributed to 30% cases of anxiety and 40% cases of depression in North America, and more than a quarter of cases of both conditions in Europe (Bellis et al, 2019). In China, adolescents with 3-5 ACEs are over 10 times likely to be depressed and more than 20 times to have suicidal attempts (Jia et al, 2020). Finally, the stress sensitization hypothesis indicated that ACEs hinder the development of brain areas in charge of stress regulations (McLaughlin et al, 2010) which could not only lead to mental health problems but also trigger subsequent new stressors that were not previously present (Aneshensel and Mitchell, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was proved that experiencing four or more ACEs is associated with smoking, drug abuse, early sexual initiation and having multiple sexual partners [15]. Furthermore, based on a research conducted by Zhihui Jia et al on a population of 884 senior high school students from Nanchang in China, it can be concluded that ACEs increase the probability of depressive symptoms, suicidal thoughts and suicidal plans [19].…”
Section: Discussionmentioning
confidence: 99%